Centralized drug procurement operation scheduling with a capacitated joint replenishment and delivery strategy: Evidence from China. (October 2022) - Liu, Rui; Zhou, Zhihao; Qin, Quande; Fan, Bi
Highlights: We propose a novel model for centralized drug procurement operation in China. An intelligent optimization approach is developed to address the proposed model. Evaluate the effectiveness of the proposed approach using a practical case. The experimental results provide some important managerial insights. Abstract: Due to the tremendous increases in the cost of providing health care systems, it is crucial importance to control the health spending. This study aims to explore the optimization of centralized drug procurement based on a capacitated joint replenishment and delivery strategy. A mixed integer nonlinear programming model is proposed to describe the practical operation process in China. The objective is to find a replenishment and delivery schedule, which operates in such a way that the total cost (including setup costs, storage costs, freight costs and cost of capital) is minimized under the constraints of production and distribution capacity. A novel hybrid optimization, composed of an ingenious memetic algorithm and a well-designed bound heuristic, is developed to solve the proposed model. The memetic algorithm includes a modified genetic operation and a local search procedure, and the bound heuristic is used to reduce the decision space substantially. The experimental results demonstrated that the proposed optimization can effectively obtain high-quality solutions, as illustrated by a comparative numerical study.